Neurotrophins : more than Neurotrophic - Shamini Ayyadhury (2010)
The Nerve Growth Factor (NGF) is the prototypic member of the neurotrophin (NT) family, which plays an essential role in the development and functioning of the vertebrate nervous system. Although originally defined by their actions on neuronal survival and differentiation in the peripheral (PNS) and central nervous systems (CNS), accumulating data indicate the presence of extensive interactions between the NTs and the immune system. NTs are released normally during lymphocyte and leukocyte development by the bone marrow and the thymus and later by secondary lymph organs to maintain responsiveness of these circulating naïve and memory immune cells. Functional NT receptors have been detected on the cells of the immune system and increased levels of NGF protein are found during the acute phase of various diseases with a significant inflammatory component. Furthermore, in certain conditions such as allergic asthma, the released NTs exacerbate the severity of the inflammation and prolong the diseased state. However, in the CNS, if one can control homeostasis of the internal environment, then the natural response of the infiltrating immune cells to release these NTs can be used to intervene at key points in the disease progression. These wider functions are likely to be of concern in any attempted therapeutic use of NGF or related NTs.